Respiratory complaints and spirometric parameters of the villagers living around the Seyitomer coal-fired thermal power plant in Kutahya, Turkey - SAVE, DİLŞAD (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2002)
The aim of the study was to investigate the respiratory effects of the stack emissions of the Seyitomer coal-fired thermal power plant in the Kutahya Province of Turkey. The three villages that are located within 5 km around the power plant were investigated as our Villages around Power Plant. Two villages which were similar to the Villages around Power Plant as far as climate, culture, and lifestyle were concerned and which were located more than 30 km away from the thermal power plant were investigated as our Control Villages. The study design was based on the comparison of the respiratory complaints and the spirometric parameters of the individuals living in the two groups of villages. The study was carried out on individuals of 15 years of age and above living in these villages (277 of 302 individuals living in the Villages around Power Plant and 225 of 264 living in the Control Villages). Among the ones living in the Villages around Power Plant, 46.2% had complaints of chest tightness and 29.2% repeated coughing attacks present for more than one year, whereas these percentages were 28.0 and 20.4% in the Control Villages, the differences being statistically significant (P = 0.001 and P = 0.024, respectively). The complaint of productive coughing present for more than one year was not found to differ statistically significantly between the two groups of villages (P = 0.0885). The means of the spirometric parameters of FEV1 and FEF25-75% were found to be statistically significantly lower in the individuals of the Villages around Power Plant compared Eo the individuals of the Control Villages (P = 0.0001 and P = 0.0001, respectively). When the spirometric parameters of nonsmokers were compared between the two groups of villages, FEV1, FVC, and FEF25-75% were found to be statistically significantly lower in the Villages around Power Plant compared to the Control Villages (P = 0.0001, P = 0.0001, and P = 0.0001, respectively). No statistically significant differences of the spirometric measurements of current smokers were observed between the two groups of villages (P > 0.05). The spirometric parameters revealed statistically significant adverse health effects of the Power Plant, this was particularly apparent for the nonsmokers. More specific tests to confirm the diagnosis of acute and chronic lung diseases can be suggested to be carried 0 out in the area in further studies. Also follow-up studies can be recommended in the area to detect any new adverse health effects of the Power Plant. (C) 2002 Elsevier Science (USA).
Keywords: coal-fired thermal power plant; spirometry; respiratory complaints; AIR-POLLUTION; SYMPTOMS; VICINITY; HEALTH